Case report: Novel homozygous ACVRL1 missense variant in a family with hereditary hemorrhagic telangiectasia and pulmonary arterial hypertension: findings suggest a hypomorphic allele - Mathavan, Akash; Mathavan, Akshay; Krekora, Urszula; Rao, Adityanarayan; Zumberg, Marc S.; Justice, Jeb; Bayrak-Toydemir, Pinar; McDonald, Jamie; Ataya, Ali (Frontiers in Genetics, 2025)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant vascular disorder caused by pathogenic variants in genes within the transforming growth factor beta (TGF-β) signaling pathway, such as ACVRL1, leading to haploinsufficiency. Homozygous variants in HHT-related genes are exceptionally rare and have not been reported in ACVRL1-related HHT to date. We report the first known instance of a novel homozygous missense variant in the ACVRL1 gene (c.576C>G; p.Phe192Leu) identified in two siblings from a family of seven, in which three heterozygotes were also present. Comprehensive clinical evaluations revealed striking phenotypic differences between the homozygous and heterozygous family members. Both homozygous individuals exhibited early-onset pulmonary arterial hypertension and diffuse pulmonary arteriovenous malformations. One of them also demonstrated childhood-onset gastrointestinal bleeding—a manifestation unprecedented in HHT that typically has a late-adulthood onset. In contrast, the heterozygotes displayed either mild or equivocal features of HHT, supporting the classification of this variant as a hypomorphic allele. The novel missense variant is located within the intracellular glycine–serine (GS) domain of the protein, suggesting potential impacts on receptor regulation and downstream signaling. Although these findings expand the phenotypic spectrum of ACVRL1-related HHT, they remain limited to clinical observations. Experimental studies, including functional and molecular assays, are therefore essential to confirm the pathogenic impacts of this variant, validate its classification as a hypomorphic allele, and elucidate its effects on BMP-TGF-β signaling.